Stress Levels in the Elderly in Facing Covid-19 at the Kawatuna Health Center - Hasnidar; Sukrang; Fauzan; Indah Rahmana Putri (Journal of Health and Nutrition Research, 2023)
Data on mortality due to Covid-19 worldwide shows an increase with age. In 2021 it was reported that the highest number of death related to Covid-19 occurred in the age range ≥ 60 years, namely 47.3%. The effects of Covid-19 make the elderly experience psychological disorders, so the stress level in the elderly increases, which can decrease the immune system. The study aimed to identify the stress level of older people in dealing with Covid-19 at the Wireuna Public Health Center. The research design used was descriptive with a survey design. The research was located in the Kabeluna Health Center, during 18-24 August 2022. The population was all elderly who visited the Kawatuna Health Center. The sample was total accidental sampling, with about 30 respondents. The data collection technique used the Dass questionnaire (Depression Anxiety Stress Scales). The results showed that 16.7% of the respondents had no stress to moderate stress (5 respondents), and 83.3% had moderate to severe stress levels (25 respondents). It is recommended that health workers increase guidance to elderly patients with various health promotion strategies, for example, teaching relaxation techniques, carrying out regular physical activities, and health counseling for monitoring and evaluating stress levels in the elderly. In this case, the nurse's role is to provide this education